(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1911)
There are some fifteenth-century documents in the Vatican archives which show that the hospital was connected with the see of Bethlehem, and that it was served by an order of canons regular whose presence in Scotland has hitherto escaped notice. The see of Bethlehem had considerable possessions but these were mostly in Europe. In a bull of 1266 under Scotland there are two entries, ’” the church of St Germains in the diocese of St Andrews, and the oratory of New Bethlehem in London. St Germains was not a parish and it is argued that the reference should be to hospital rather than church. In the middle of the thirteenth century the Bethlehemite hospitallers were established in London and at St Germains. The order was one of canons regular of St Augustine.